2008
DOI: 10.1002/aoc.1392
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium N‐heterocyclic–carbene catalyzed diarylation of arene CH bond

Abstract: Novel ruthenium-1,3-dialkylimidazolin-2-ylidene complexes (2a-e) have been prepared and characterized by C, H, N analysis, 1 H-NMR and 13 C-NMR. The ortho position of the aromatic ring of pyridyl group substituted aromatic compound was directly arylated with aryl bromides and chlorides in the presence of a catalytic amount of [RuCl 2 (1,3-dialkylimidazolin-2-ylidene)] complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 59 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…These complexes show typical spectroscopic signatures, which are in line with those recently reported for other [PdCl 2 (N-heterocyclic carbene) 2 ] complexes. [18,19,27] The analytical data are in good agreement with the compositions proposed for all the complexes and are summarized in Table 2.…”
Section: Resultssupporting
confidence: 76%
“…These complexes show typical spectroscopic signatures, which are in line with those recently reported for other [PdCl 2 (N-heterocyclic carbene) 2 ] complexes. [18,19,27] The analytical data are in good agreement with the compositions proposed for all the complexes and are summarized in Table 2.…”
Section: Resultssupporting
confidence: 76%
“…Further investigation of the potential of these ligands revealed their high efficiency in direct C sp 2 −H arylation . The direct arylation of “inert” C−H bonds is currently a field of high interest, notably for its faculty to minimize the organometallic waste produced with classical cross-coupling reactions .…”
Section: Group 8: Iron Ruthenium and Osmiummentioning
confidence: 99%
“…Subsequently, Özdemir and co-workers synthesized a series of well-defined, air- and moisture-stable Ru–NHC complexes 206 – 209 based on the imidazolidinylidene scaffold and evaluated their activity in (sp 2 )–H arylation of 2-arylpyridines with aryl chlorides (Scheme ). They found that these [Ru­(NHC)­Cl 2 ] complexes are highly active in the diselective arylation of 2-arylpyridines. Catalyst comparison studies demonstrated that precatalyst 209 containing the N -4-methylbenzyl substituent was the most active in this series.…”
Section: Ruthenium–nhc Complexesmentioning
confidence: 99%
“…with aryl chlorides (Scheme 139). 275 They found that these [Ru(NHC)Cl 2 ] complexes are highly active in the diselective arylation of 2-arylpyridines. Catalyst comparison studies demonstrated that precatalyst 209 containing the N-4methylbenzyl substituent was the most active in this series.…”
Section: Ruthenium−nhc Complexesmentioning
confidence: 99%